1991
DOI: 10.1104/pp.97.4.1462
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Tomato Acid Phosphatase Complementary DNA Associated with Nematode Resistance

Abstract: The tomato (Lycopersicon esculentum) acid phosphatase-1 (Apase-11, EC 3.1.3.2) isozyme variant, genetically linked to the root-knot nematode resistance locus (Mi) on chromosome 6, has been purified by a rapid procedure from tomato cell suspension cultures. Peptide fragments of the purified enzyme were generated from trypsin and Lys-C endoprotease digests and separated by reverse-phase high-performance liquid chromatography. Amino acid sequences derived from the purified peptide fragments represented >50% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The first plant gene to be classified as an ACP was from tomato, although interest in it was primarily due to its tight genetic linkage to a root-knot nematode-resistance gene rather than to its enzymic activity (Aarts et al, 1991;Erion et al, 1991;Williamson and Colwell, 1991). The other plant AP that has been cloned and sequenced is the soybean VSP (Staswick 1988;Dewald et al, 1992), which has been shown to possess some phosphatase activity (Dewald et al, 1992).…”
mentioning
confidence: 99%
“…The first plant gene to be classified as an ACP was from tomato, although interest in it was primarily due to its tight genetic linkage to a root-knot nematode-resistance gene rather than to its enzymic activity (Aarts et al, 1991;Erion et al, 1991;Williamson and Colwell, 1991). The other plant AP that has been cloned and sequenced is the soybean VSP (Staswick 1988;Dewald et al, 1992), which has been shown to possess some phosphatase activity (Dewald et al, 1992).…”
mentioning
confidence: 99%
“…These sequences shared 64, 56, and 54% identity, respectively. The LASAP1 sequence, however, had no significant homology with other types of APases, such as tomato APSl (Aarts et al 1991;Erion et al 1991Erion et al , 1992Williamson and Colwell 1991;Tanaka et al 1992). In KBPAP, 7 metal-binding sites and a general active site have been identified from the crystal structure (Strater et al 1995).…”
Section: Resultsmentioning
confidence: 94%
“…The deduced amino acid sequence of the PSP cDNA was found to have 71 and 65% identity with those of VSP-LU and VSP-p of soybean, respectively (Rhee and Staswick, 1992a, 199213). PSP also had 40% sequence identity with tomato acid phosphatase-1 (Erion et al, 1991). The amino acid sequences of acid phosphatase-1 and VSP share about 45% identity.…”
Section: Cenomic Southern Blot Analysismentioning
confidence: 92%
“…The N-terminal amino acid sequence of forms A and C of PSP corresponded to amino acid residues 37 to 52. The deduced amino acid sequence of the APSP1 cDNA has 71 and 65% identity with those of VSP-a and VSP-/3 of soybean, respectively Staswick, 1992a, 1992b), and 40% identity with acid phosphatase-1 of tomato (Erion et al, 1991). No putative glycosylation sites were contained in the deduced amino acid sequence of APSP1 cDNA (Fig.…”
Section: Nucleotide Sequence Of Psp Cdnamentioning
confidence: 98%
See 1 more Smart Citation